Scheduling of Power Generation A Large-Scale Mixed-Variable Model - Prékopa, András; Mayer, János; Strazicky, Beáta; Deák, István; Hoffer, János; Németh, Ágoston; Potecz, Béla (Springer Series in Operations Research and Financial Engineering, 2014)
The book contains description of a real life application of modern mathematical optimization tools in an important problem solution for power networks. The objective is the modelling and calculation of optimal daily scheduling of power generation, by thermal power plants,  to satisfy all demands at minimum cost, in such a way that the  generation and transmission capacities as well as the demands at the nodes of the system appear in an integrated form. The physical parameters of the network are also taken into account. The obtained large-scale mixed variable problem is relaxed in a smart, practical way, to allow for fast numerical solution of the problem.